Effects of Perilla (Perilla frutescens L.) Meal as Partial Replacement for Soybean Meal on Metabolizability, Performance, and Carcass Characteristics of Broilers - MONTHA, Napatsorn; YOTHINSIRIKUL, Winai; TIPPAYA, Kittipong; KREUZER, Michael; JATURASITHA, Sanchai (Walailak Journal of Science and Technology (WJST), 2021)
There is an ongoing search for novel protein sources suitable to replace soybean meal. The present study aimed to investigate the utility of cold-pressed perilla seed meal for broiler diets. Perilla meal was included at dietary levels of 0, 4, and 8 %. In the first experiment, apparent digestibility and metabolisability of nutrients were performed with 24 Cobb 500 broilers. In the second experiment, growth performance and carcass quality were investigated in 120 Cobb 500 broilers. The inclusion of perilla meal into the diet in an iso-nitrogenous way increased feed intake and metabolisability of nitrogen but decreased the digestibility of fat and fiber as well as the metabolisability of energy. The highest proportion of perilla meal enhanced the growth performance. Carcass weight and dressing percentage did not differ among groups. Proportions of total retail cuts and, among them, breast meat and thighs, were elevated by using perilla meal, especially at a level of 8 %. The proportion of abdominal fat declined with increasing levels of perilla meal. In conclusion, perilla meal turned out to be a valuable protein source in broiler nutrition. It also showed that part of the soybean meal could be replaced without risking adverse effects on growth performance and carcass quality.